2017
DOI: 10.1088/1475-7516/2017/11/003
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on dark matter models from the observation of Triangulum-II with the Fermi Large Area Telescope

Abstract: Triangulum-II, a newly discovered dwarf spheroidal galaxy, is a strong candidate for the indirect search of dark matter through the detection of γ-ray emission that could originate from the pairannihilation of weakly interacting massive particles (WIMPs). We here report on the analysis of almost seven years Fermi Gamma-Ray Space Telescope data of Triangulum-II which was taken during its all sky survey operation mode. No excess γ-ray emission has been detected above 100 MeV from Triangulum-II. We derive the upp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…γ-flux upper limit for Γ = 1 is almost 2 orders of magnitude lower than the one corresponding to Γ = 2.4. This result is consistent with our previous work for Triangulum-II (Tri-II) [66], in which we have also found that the flux upper limit in 95 % C.L. is increased by increasing the spectral indices.…”
Section: Results Of the Power-law Modelingsupporting
confidence: 93%
“…γ-flux upper limit for Γ = 1 is almost 2 orders of magnitude lower than the one corresponding to Γ = 2.4. This result is consistent with our previous work for Triangulum-II (Tri-II) [66], in which we have also found that the flux upper limit in 95 % C.L. is increased by increasing the spectral indices.…”
Section: Results Of the Power-law Modelingsupporting
confidence: 93%
“…Overall, in all these cases, due to the stringent flux density limits, our results put comparable limits as some of the recent works (e.g. Archambault et al 2017;Biswas et al 2017;Bhattacharjee et al 2019;Vollmann et al 2020) from other radio as well as high energy observations of the dSph galaxies.…”
Section: Constraints On Dark Mattersupporting
confidence: 89%
“…5(a,b) and 6, we can notice that none of the LSB galaxies have put any constraint on any of these above mentioned theoretical models. The LAT sensitivities obtained from these four LSB galaxies are nearly 3 orders higher than the LAT sensitivity estimated from Tri-II [19]. Hence, from Figs.…”
Section: Constraints On the Annihilation Cross-sectionmentioning
confidence: 59%
“…(a,b) and Fig. 6, we have also compared the LAT-sensitivity obtained from LSB galaxies with newly discovered ultra faint dwarf spheroidal (dSph) galaxy, Triangulum-II (Tri-II) [19] for its two different values of velocity dispersion σ. In Fig 5(a,b), we have considered two DM particle models, namely, minimal supergravity (mSUGRA) [57] and Minimal Supersymmetric Standard Model (MSSM) [58].…”
Section: Constraints On the Annihilation Cross-sectionmentioning
confidence: 99%
See 1 more Smart Citation